2017
DOI: 10.1128/jvi.01656-16
|View full text |Cite
|
Sign up to set email alerts
|

Activation of COX-2/PGE 2 Promotes Sapovirus Replication via the Inhibition of Nitric Oxide Production

Abstract: Enteric caliciviruses in the genera Norovirus and Sapovirus are important pathogens that cause severe acute gastroenteritis in both humans and animals. Cyclooxygenases (COXs) and their final product, prostaglandin E2 (PGE2), are known to play important roles in the modulation of both the host response to infection and the replicative cycles of several viruses. However, the precise mechanism(s) by which the COX/PGE2 pathway regulates sapovirus replication remains largely unknown. In this study, infection with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 44 publications
(58 reference statements)
1
30
1
Order By: Relevance
“…The same study also suggested that increased COX-2 expression in 5-LOX and 15-LOX deficient macrophages was responsible for the defect in M2 polarization. Indeed, several recent studies have implicated COX-2 derived PGs in detrimental immune responses during viral infection, including virus-induced immunosuppression (Chen et al, 2015;Gandhi et al, 2015;Alfajaro et al, 2017).…”
Section: Viral Infectionmentioning
confidence: 99%
“…The same study also suggested that increased COX-2 expression in 5-LOX and 15-LOX deficient macrophages was responsible for the defect in M2 polarization. Indeed, several recent studies have implicated COX-2 derived PGs in detrimental immune responses during viral infection, including virus-induced immunosuppression (Chen et al, 2015;Gandhi et al, 2015;Alfajaro et al, 2017).…”
Section: Viral Infectionmentioning
confidence: 99%
“…NSAIDs could also affect a later stage of the SARS-CoV-2 life cycle. For porcine sapovirus, feline calicivirus, murine norovirus, and mouse coronavirus, COX inhibition impaired viral replication (6,9,10). COX inhibition was found to impair mouse coronavirus infection at a post-binding step early in the replication cycle, potentially entry or initial genome replication (6).…”
Section: Introductionmentioning
confidence: 98%
“…The cytotoxicity test for the different chemicals used was carried out by a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay as described previously [ 34 , 63 ]. Briefly, monolayers of RAW264.7 and CRFK cells grown in 96-well plates were incubated for 24 h with different concentrations of chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…To evade this, viruses devise strategies to subvert cellular pathways for their own benefit such as via COXs/prostaglandin E 2 (PGE 2 ) signaling, which participates in the modulation of the host response to infection and the life cycle of several viruses [ 32 33 ]. Representatives from at least eleven different virus families are known to activate COXs/PGE 2 signaling or to enhance the expression levels of PGE 2 : Caliciviridae [ 34 ], Arteriviridae [ 35 ], Herpesviridae [ 36 ], Rhabdoviridae [ 37 ], Retroviridae [ 38 ], Picornaviridae [ 39 40 ], Flaviviridae [ 41 ], Orthomyxoviridae [ 42 43 ], Adenoviridae [ 44 ], and Paramyxoviridae [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation